Genetic diversity and novel haplotypes of Apis mellifera jemenitica on the Arabian Peninsula: insights from mtDNA markers - Alsharhi, Mohammed; Al-Ghamdi, Ahmad; Al-Garadi, Maged Ahmed; Alburaki, Mohamed (Frontiers in Genetics, 2025)
The genetic diversity of Apis mellifera jemenitica populations collected from the Arabian Peninsula (Saudi Arabia, Yemen, and Oman), Jordan, and Ethiopia, was examined using three mtDNA markers: 1- Cytochrome b (Cyt b), 2- Cytochrome c oxidase I (COI) and 3- The intergenic region located between the cytochrome c oxidase I & II (COI-COII). DNA was extracted from 44 samples, amplified for each region using classic PCR, and the resulting amplicons were sequenced using Sanger technology at both ends. Sequences were verified and aligned, and Maximum-Likelihood phylogenetic analyses were conducted with reference sequences from other subspecies. The in silico DraI mtDNA COI-COII (DmCC) test was applied to the COI-COII sequences to identify evolutionary lineages and haplotypes. Moreover, COI-COII haplotype network analyses were conducted to assess the intra- and inter-genetic relationships between samples and references. Based on the Cyt b marker, most samples cluster within the African lineage (A) near lamarckii and syriaca (Sub-lineage Z) subspecies. Few samples from Ethiopia and Yemen were closely related to simensis and scutellata clades. The COI gene separated jemenitica samples (Bootstrap = 97) from subspecies of other lineages (C and O). The DmCC test revealed a P0Q2 structure in the intergenic region for all samples, with a distinct 18 bp deletion in the P0 element observed in two Ethiopian and one Yemeni samples, suggesting litorea or simensis origin. A total of 13 COI-COII haplotypes were identified, among which 8 haplotypes were novel: Saudi Arabia (1), Yemen (3), Oman (1), and Ethiopia (3), with a haplotype diversity (H) of 0.980. Furthermore, molecular-variance parsimony in COI-COII confirmed a distant genetic relationship between Ethiopian samples versus samples of the Arabian Peninsula. The haplotype network analysis suggests a higher intra-jemenitica diversity than previously understood with a syriaca ancestry to this clade. These findings offer crucial insights into the conservation of A. m. jemenitica and its role in preserving biodiversity in arid ecosystems. Additionally, the data enhance our understanding of the genetic diversity of A. m. jemenitica and its evolutionary connections with other neighboring African subspecies.